Akurasi dan Evaluasi Terjemahan Arab-Indonesia dalam Takarir Film “From the Ashes” (2024) - Nurhayati, Peti; Maulani, Abdullah; Suparno, Darsita; Abdullah, Abdullah (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2025)
This research aimed at analyzing the translation quality and cultural adaptation aspects in a translated movie of